Comprehensive investigation on wear and microstructure development in Al/ti ultrafine grained multi-layered composite produced by Accumulative Roll Bonding (ARB). (16th October 2019) - Sadeghinia, H; Jafarian, H R; Salehi, M T; Eivani, A R
Abstract: In this study, a multi-layered ultrafine-grained Al/Ti composite was produced by accumulative roll bonding (ARB). Microstructure and the mechanical properties of the composite was characterized by scanning electron microscope (SEM), x-ray diffraction (XRD), tensile testing, hardness and wear tests. It was found that in microstructural studies the Ti layer fractured locally with increasing the ARB cycle. As well, a better distribution of Ti particles is obtained with increasing the ARB cycle. The XRD results showed that intermetallic compound was not formed between Al and Ti layers. Also, the results proved that with increasing the ARB cycle, strength and hardness of the composite were increased, but elongation was reduced. Surprisingly, the tensile elongation of the 1-cycle ARB processed multi-layered composite is higher comparing to others. Finally, wear test assessment showed that the wear resistance of the composite was improved about 2.5 times more than the starting material of Al.